Energy Policy For Sustainable Development In Malaysia. - Mohamed, Abdul Rahman; Lee, Keat Teong (2004)
Energy is crucial to all aspects of development from powering manufacturing and modernization of agricultural sectors to providing electricity to run schools and health facilities, yet the impact of its production, distribution and use grows more severe with every decade.